RISIKO KREDIT BANK UMUM KONVENSIONAL (STUDI PADA BANK PERSERO 2010-2021) - Yustian, Lila Denayu; Zuhroh, Idah (Program Studi Ekonomi Pembangunan, 2021)
This study aims to provide an overview of developments and determine credit risk at Conventional Commercial Banks. The independent variables in this study are Expenses and Income operational (BOPO), Capital Adequacy Ratio (CAR) and inflation for Non Performing Loan (NPL). The population used in this study is a registered Conventional Bank in Otoritas Jasa Keuangan (OJK) as many as five bank. The sample of this research is using 4 banks by using sampling method is purposive sampling. The result for this research are BOPO has a positive and significant effect on NPL. CAR has a negatife and significant effect on NPL Inflation has a negative and significant effect on NPL.